Controlling fibrous capsule formation through long-term down-regulation of collagen type I (COL1A1) expression by nanofiber-mediated siRNA gene silencing - Rujitanaroj, Pim-On (2013)
The foreign body reaction often interferes with the long-term functionality and performance of implanted biomedical devices through fibrous capsule formation. While many implant modification techniques have been adopted in attempts to control fibrous encapsulation, the outcomes remained sub-optimal. Nanofiber scaffold-mediated RNA interference may serve as an alternative approach through the localized and sustained delivery of siRNA at implant sites. In this study, we investigated the efficacy of siRNA–poly(caprolactone-co-ethylethylene phosphate) nanofibers in controlling fibrous capsule formation through the down-regulation of collagen type I (COL1A1) in vitro and in vivo. By encapsulating complexes of COL1A1 siRNA with a transfection reagent (Transit TKO) or the cell penetrating peptides CADY or MPG within the nanofibers (550–650 nm in diameter), a sustained release of siRNA was obtained for at least 28 days (loading efficiency ∼60–67%). Scaffold-mediated transfection significantly enhanced cellular uptake of oligonucleotides and prolonged in vitro gene silencing duration by at least 2–3 times as compared to conventional bolus delivery of siRNA (14 days vs. 5–7 days by bolus delivery). In vivo subcutaneous implantation of siRNA scaffolds revealed a significant decrease in fibrous capsule thickness at weeks 2 and 4 as compared to plain nanofibers (p < 0.05). Taken together, the results demonstrated the efficacy of scaffold-mediated siRNA gene-silencing in providing effective long-term control of fibrous capsule formation.